Analisa Kegagalan Elevator Nerak Tipe WB 250 Untuk Mengangkut Sulfur Granulation Di PT. Medco E&P Malaka - Hamdani, Hamdani; Fakhriza, Fakhriza; Saputra, Hendra; Bahri, Samsul; Saputra, Edi (VOCATECH: Vocational Education and Technology Journal, 2025)
AbstractPT. Medco EP Malaka operates one unit of the Nerak WB 250 elevator located in the Sulfur Granulation Unit (SGU), which functions as a material handling system for transferring granulated sulfur from the steel belt conveyor to the sulfur silo. This elevator is driven by an electric motor and gearbox connected to the driver idler shaft (head pulley). The driver idler rotates the rubber chain equipped with buckets containing sulfur granules, allowing the material to be transported vertically to the sulfur silo. However, frequent failures have occurred in several elevator components such as the rubber chain, snap ring, bucket rod, clamping sleeve, chain bushing, bucket, tension idler, as well as the upper and lower idlers. To analyze these failures, the Root Cause Analysis (RCA) method was employed using the Why-Why-Why Analysis (W3A) approach, which is a commonly used method at PT. Medco EP Malaka. Based on field observations and W3A analysis results, the main causes of failure were identified as misalignment in the elevator system due to worn idler bushings, detached snap rings, and malfunctioning proximity sensors—further aggravated by suboptimal preventive and predictive maintenance activities. Additional contributing factors include clumped sulfur accumulation, which increases the system load. Based on these findings, corrective actions were taken and improvements were made to strengthen both the Predictive Maintenance (PdM) and Preventive Maintenance (PM) programs in order to ensure the reliability of the NERAK WB 250 elevator system at the SGU.Keywords:Elevator Nerak; Sulfur Granulation; Maintenance; Root Cause Analysis (RCA)   AbstrakPT. Medco EP Malaka mempunyai 1 unit mesin elevator Nerak WB 250 yang ada pada Sulfur Granulation Unit (SGU) yang berfungsi sebagai alat pemindah sulfur yang sudah berbentuk granul dari steel belt conveyor menuju sulfur silo. Elevator ini digerakkan menggunakan motor listrik beserta gearbox yang terhubung ke shaft driver idler (head pulley). Driver idler memutar rubber chain yang dilengkapi dengan bucket berisi sulfur granul sehingga material dipindahkan secara vertikal menuju sulfur silo. Namun, sering terjadi kerusakan pada komponen elevator seperti rubber chain, snap ring, bucket rod, clamping sleeve, chain bushing, bucket, tension idler, upper dan lower idler. Untuk menganalisis kegagalan tersebut, digunakan metode Root Cause Analysis (RCA) dengan pendekatan Why-Why-Why Analysis (W3A), yang merupakan metode yang lazim digunakan di PT. Medco EP Malaka. Berdasarkan temuan lapangan dan hasil analisa W3A, diketahui bahwa penyebab utama kegagalan adalah misalignment pada sistem elevator akibat ausnya bushing idler, lepasnya snap ring, serta tidak berfungsinya proximity sensor, yang diperburuk oleh kurang optimalnya kegiatan preventive dan predictive maintenance. Faktor lain seperti tumpukan sulfur yang menggumpal dan menyebabkan beban lebih juga turut berkontribusi terhadap kegagalan sistem. Berdasarkan hasil analisa tersebut, dilakukan tindakan perbaikan serta penguatan program Predictive Maintenance (PdM) dan Preventive Maintenance (PM) agar keandalan sistem elevator NERAK tipe WB 250 di SGU dapat terjaga dengan baikKata Kunci:                                                  Pemilihan tindakan; Perawatan; Root Cause Analysis (RCA)